The Relationship Between Combined Nitrogen Uptakes and Nitrogen Fixation in Azolla-Anabaena Symbiosis - Ito, Osamu; Watanabe, Iwao (Wiley, 1983)
The assimilation and distribution in Azolla pinnata of nigrogen from three different sources of nitrogen–ammonium, nitrate and dinitrogen–were compared. Neither ammonium nor nitrate supplied at 1 mM for 4 days, inhibited acetylene reduction activity (ARA). At higher concentrations, the ARA was less inhibited by nitrate than by ammonium. Of the three nitrogen sources tested, nitrate‐nitrogen was the least available and mobile in Azolla.After incubation with 15N‐labelled nitrogen sources leaves were divided into six branches ranging from young to the old and the distribution of 15N among those branches determined. Ammonium and dinitrogen were preferentially assimilated into younger branches and nitrate into older ones.Alternative labelling with either dinitrogen or combined nitrogen showed that dinitrogen fixation took place simultaneously with the assimilation of ammonium or nitrate, and was less inhibited by nitrate than by ammonium. After 4 days of incubation, about a half of the total nitrogen in Azolla comprised nitrogen newly incorporated from both the medium and atmosphere, and of this about 70 and 30% originated from ammonium and nitrate at 10 mM respectively.It is suggested that, even when Azolla is grown on a medium containing combined nitrogen, Anabaena in the leaf cavities still fixes atmospheric nitrogen and supplies it to the host plants, and that each nitrogen source is incorporated and translocated in a characteristic manner.